Adsorption of anionic dyes in aqueous solution using chemically modified barley straw - Ibrahim, Shariff; Fatimah, I.; Ang, Ming; Wang, Shaobin (International Association on Water Quality, 2010)
An agricultural waste derived adsorbent was prepared by chemically modified barley straw with NaOH and a cationic surfactant hexadecylpyridinium chloride monohydrate (CPC). The prepared adsorbent, BMBS, was used for removal of anionic dyes; Acid Blue (AB40) and Reactive Blue 4 (RB4) from aqueous solution in a batch adsorption system. The adsorbent was characterized by FT-IR and elemental composition. The stability of CPC adsorbed on straw surface was also evaluated by exposing to aqueous solution. In adsorption tests, influence of operation parameters such as contact time, initial concentration and pH of solution on AB40 and RB4 uptake were investigated and discussed. The CPC was observed strongly attached to straw surface and removal percentage of AB40 and RB4 was increased with increasing in contact time. The adsorption of dyes on modified straw surface was favorable at high acidic condition and desorption was found relatively low upon exposing to the desorption agent (i.e water). Dynamic experiment revealed that the kinetic data fitted well to the pseudo-second-order model for both of the dyes. The isotherm study also indicated that RB4 and AB40 adsorption suited well with the Langmuir model, The maximum adsorption capacity determined from the Langmuir isotherm at 25°C was 51.95 mg g-1 and 31.5 for AB40 and RB4, respectively.